Statistical test for your quantitative research project - Nik Abdul Rahman, Nik Suryani (IIUM Press, International Islamic University Malaysia, 2018)
Statistics are quantitative methods of describing, analyzing, and drawing inferences or conclusions from data. This book is written for users to know how to properly select the right statistical test, present and describe information, draw conclusions about large populations based only on information obtained from samples. It is hoped that users of this book will ultimately be able to solve real-life problems and make sensible, valid, and reliable decisions on the basis of the statistical analysis conducted with confidence.